2017
DOI: 10.1161/atvbaha.117.309913
|View full text |Cite
|
Sign up to set email alerts
|

NO Augments Endothelial Reactivity by Reducing Myoendothelial Calcium Signal Spreading

Abstract: Our results identify a novel mechanism by which NO can increase the efficacy of calcium, rising vasoactive agonists in the microvascular endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…For details, see following reviews: 56,86,92 Of note, the important role of phosphorylation implies a complementary role of phosphatases in the regulation of connexin functionalities. 67,102,103 Connexin C-terminus phosphorylations not only affect channel permeability but also gap junction turnover 56,61 as well as interaction of the C-terminus with other proteins. 104,61 The latter appears to be pivotal for the control of interactions with other proteins, which are involved in the control of channel-independent functions of proteins.…”
Section: Regulatory Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For details, see following reviews: 56,86,92 Of note, the important role of phosphorylation implies a complementary role of phosphatases in the regulation of connexin functionalities. 67,102,103 Connexin C-terminus phosphorylations not only affect channel permeability but also gap junction turnover 56,61 as well as interaction of the C-terminus with other proteins. 104,61 The latter appears to be pivotal for the control of interactions with other proteins, which are involved in the control of channel-independent functions of proteins.…”
Section: Regulatory Principlesmentioning
confidence: 99%
“…Its phosphorylation is controlled by the NO-sensitive tyrosine phosphatase SHP-2. 102 Additionally, the NO-induced blockade of MEGJ results in a prolonged elevation of calcium in the endothelium since the underlying smooth muscle can no longer act as a calcium sink. 55 We suggest that this mechanism may improve the vasomotor effects of the endothelium by enhancing calcium-dependent endothelial autacoid synthesis in the microcirculation.…”
Section: F I G U R Ementioning
confidence: 99%
“…One of the most important signaling molecules which participates in the vascular tone is Ca +2 , which initiates the contraction in smooth muscle. The elevation of Ca +2 concentrations within the endothelium activates a negative feedback loop by increasing the synthesis of vasoactive molecules such as NO and endothelium-derived hyperpolarization factor (EDHF), promoting the relaxation of the vessels [125]. EDHF, an endothelium-derived vasodilator, is crucial in small arteries, and although there is no clarity as to the precise nature of this molecule, it seems that it is permeable through gap junctions, since a good correlation between the presence of functional gap junction and the activity of EDHF [126][127][128] has been demonstrated.…”
Section: The Role Of Hemichannels and Gjcs In The Vasculaturementioning
confidence: 99%
“…In the presence of NO, Cx37-mediated gap junction communication is diminished [125,145,146]. Pogoda and co-workers demonstrated that in HeLa cells, this mechanism includes the inhibition of a tyrosine phosphatase (SHP-2), which removes the phosphorylation in tyrosine residue 332 on the C-terminal region of Cx37.…”
Section: Could Hemichannels and Gjcs Mediate Part Of The Ros/rns Respmentioning
confidence: 99%
“…However, unlike Cx43, the effects of NO on Cx37 gap junction channels are thought to be indirect, with no known cysteine modification occurring. Rather, the phosphorylated tyrosine residue (Cx37-Tyr332) is protected from de-phosphorylation by Src homology region 2 (Shp2) phosphatase, which is inhibited in the presence of NO, reducing MEJ transfer of Ca 2+ signaling through Cx37 GJ [ 261 ]. Thus, S -nitrosylation appears to have diverse effects, depending on GJ composition particularly at the MEJ [ 261 ].…”
Section: Post-translational Regulation Of Connexinsmentioning
confidence: 99%